AN OVERVIEW OF NASAL LUBRICANT FORMULATION - Amal, Surya; Sri Suriati Amal, Andi; Hidayah, Himyatul; Violina, Sriyani (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this overview is to provide information on current research and literatures relating to nasal lubricants. Drawing upon the MEDLINE database from 1945 to 2011, in addition to other relevant sources, this overview specifically discusses and evaluates various formulations and usages of nasal lubricant, their mechanism of action, associated with nasal irrigation, as well as additives used in nasal lubricant products. It is found that although nasal irrigation or nasal lubricant basically serves the same purpose and represents a costeffective method of alleviating symptoms of nasal diseases, the effects of additives used in their formulations have yet to be carefully studied.